Plyometric Hurdle Jump Training Using Beach Sand Media Increases Power and Muscle Strength in Young Adult Males - Arif Bulqini; Achmad Widodo; Nurhasan; Heriyanto Nur Muhammad; Shidqi Hamdi Pratama Putera; Anindya Mar'atus Sholikhah (OVS LLC, 2023)
The study purpose was to analyze the effectiveness of the different effects of knee tuck jump and hurdle jump plyometric training using beach sand on power and leg muscle strength in young adult males. Materials and methods. A total of 30 young adult males were enrolled in this study and were given plyometric knee tuck jump training (KTJT), and plyometric hurdle jump training (HJPT). Plyometric training is carried out with an intensity of 80-100% of 1RM, three sets with 12 repetitions each set, with a frequency of three times each week for six weeks. The measurement of leg muscle power uses the Jump Meter Digital (MD) Test, while the measurement of leg muscle strength uses the Back & Leg Dynamometer. Statistical analysis used one-way ANOVA and continued with the Least Significant Difference (LSD) post hoc test. Results. The results of the analysis are as follows: the mean ∆ increase in muscle power on CTRL (12.92±2.51 joule) vs. KTJT (142.88±35.21 joule) vs. HJPT (269.49±138.06 joule), (p=0.000). The mean ∆ increase in muscle strength on CTRL (11.61±1.49 kg) vs. KTJT (75.49±18.53 kg) vs. HJPT (137.43±34.13 kg), (p=0.000). Conclusions. Based on the results of the study, it was concluded that both types of plyometric training improve power and strength in young adult males.